Potency of Leaf Water Extract Karamunting (Rhodomyrtus tomentosa) for Enhancing GLUT4 Translocation in Diabetic Rats - Saleh, Irsan; Sutandar, Vivi Hendra; Amrina; Ningrum, Evi Dodik Novita; Sinaga, Ernawati (Science and Technology Indonesia, 2026)
Insulin resistance and damage in the pancreas are associated with type 2 diabetes, which is a chronic disease affecting health, with 422 million people affected in 2016 and 1.5 million deaths related to diabetes in 2012. Several proinflammatory mediators, such as TNF-a andIL-6, may be involved in insulin resistance in T2DM. GLUT4 is one of the glucose transporters that help promote glucose uptake. GLUT4 activation is insulin-dependent in regulating glucose uptake. Karamunting (Rhodomyrtus tomentosa (Ait.) Hassk.) leaf water extract consists of alkaloids, flavonoids, triterpenoids, saponins, and tannins. This study proposes to investigate the potential of karamunting (R. tomentosa) leaf water extract to enhance glucose uptake by modulating GLUT4 translocation in the serum and skeletal muscle of diabetic rats. The dose variations used in this study were 100 mg/kgBW, 200 mg/kgBW, and 400 mg/kgBW. Based on the results, oral administration of karamunting water extract increases GLUT4 expression in serum. It increases GLUT4 mRNAlevels in the skeletal muscle of the diabetic rat. It decreases TNF-a and IL-6 expression, with a 100 mg/kg BW dosage being the most effective. Meanwhile, 100 mg/KgBW is the most effective dosage for decreasing HOMA IR. These results indicate that karamunting (R. tomentosa) leaf water is antidiabetic by lowering TNF-a, IL-6, and HOMA IR in diabetic rats while increasing GLUT4.